Influence of Acid Wash on the Structural and Catalytic Properties of the Hierarchical Zeolite Y. Issue 5 (20th April 2016) - Li, Wenlin; Tu, Chunyan; Zheng, Jinyu; Luo, Yibin; Da, Zhijian
Abstract: Although the hierarchical architectures of zeolites are important, the precise control of their acidities also has a great influence on their catalytic properties. The hierarchical zeolite Y with high mesoporosity and well crystal structure was prepared. Then this hierarchical zeolite Y was washed with acid solution for different time. It was found that very limited mesopores formed during this acid wash procedure. However, their acidities characteristics changed dramatically. It has been found that the Brønsted acidities increased with acid wash procedure for a short time. If acid wash was performed on the resultant sample for a long time, the Lewis acidities begin decreased and the B/L ratio increased, which was most likely the result of removal of tetrahedrally coordinated EFAl species formed during desilication. This study showed that the improved accessibility of the active sites and the persevered crystallinity of the hierarchical zeolite Y were both responsible for the increased catalytic activities and an appropriate acid wash treatment comprised a powerful approach to tune the functions and catalytic properties of hierarchical zeolites Y. Abstract : Hierarchical zeolite Y: The precise control of their acidities of hierarchical zeolite has a great influence on their catalytic properties. The Brønsted acidities, Lewis acidities and B/L ratios of hierarchical zeolite Y changes significantly with acid wash. The active sites, acidities and the crystallinity of the hierarchical zeolite Y are all responsible for the activity in catalytic reaction.